Vegetation Cover Change Analysis of Phytogeographic Regions of Turkey Based on CORINE Land Cover Datasets from 1990 to 2018 - Aktürk, Emre; Güney, Kerim (Kastamonu University, 2021)
Abstract
Aim of study: The current state of the land cover and its temporal changes are one of the most popular topics nowadays, and it is a very useful subject in the protection of ecosystems and combating global climate change. The main objective of this study was to reveal vegetation cover change on Turkey and its phytogeographic region within the last 28 years.
Area of study: The study area borders of the Republic of Turkey, covers an area of 779.646 square kilometers. In addition, Turkey is home to three phytogeographic regions (Mediterranean, Euro-Siberia, and Irano-Turanian) with different floristic features. Both phytogeographic regions and Turkey were examined individually in this study.
Material and methods: 1990, 2000, 2006, 2012, and 2018 CORINE land cover datasets were used in order to examine vegetation cover of the Republic of Turkey and its phytogeographic regions in this study.
Main results: According to the results, it was determined that forests and sparsely vegetated areas decreased in the period from 1990 to 2018. It has been observed that the change in forests mainly caused by the reduction in mixed forest stands. In general, all phytogeographic regions have shown their characteristic features in the last 28 years.
Highlights: The quantitative and statistical results obtained within this study are considered to be decisive for the actions to be implemented in the upcoming years.
Keywords:
Keywords: Vegetation Cover; CORINE; Phytogeography; GIS; Remote Sensing; Vejetasyon Örtüsü; CORINE; Fitocoğrafya; CBS; Uzaktan Algılama; 13. Climate action; 15. Life on land